The Aqueous Extract of Dacryodes edulis (Burseraceae) Leaves Inhibits Cell Proliferation Induced by Estradiol on the Uterus and Vagina of Ovariectomized Female Wistar Rats - Marius Trésor Wego Kamgaing; Marie Alfrede Mvondo; Sylviane Laure Poualeu Kamani; Stéphane Minko Essono; Sylvie Lea Wansi Ngnokam (Advances in Pharmacological and Pharmaceutical Sciences)
Proliferation is a cellular process strongly linked to the genesis of cancer. Natural substances with antiproliferative activities are currently potential alternatives in the treatment of cancers. Dacryodes edulis, for instance, is a medicinal plant traditionally used in the treatment of cancer. Scientific studies have reported the antioxidant activity of this plant. In addition, the presence of prostate cancer chemopreventive polyphenols was reported in D. edulis extracts. Therefore, this study was aimed to evaluate the effects of the aqueous extract of D. edulis leaves on cell proliferation induced by estradiol in ovariectomized female Wistar rats. In this regard, ovariectomized (OVX) rats were cotreated with estradiol valerate (E2V) (0.75 mg/kg) and the aqueous extract of D. edulis leaves. Control groups received either the vehicle (sham-operated animals and the OVX control), E2V (0.75 mg/kg) only, or E2V (0.75 mg/kg) and tamoxifen (10 mg/kg). Treatments were administered orally for 3 consecutive days, and animals were sacrificed thereafter. Epithelial heights of the uterus and vagina were assessed. Uterine levels of total cholesterol and estradiol were determined as well. Results showed that the aqueous extract of D. edulis leaves reversed the effects of estradiol as it reduced uterine weight (p<0.05), uterine (p<0.05), and vaginal (p<0.001) epithelium heights. This antiproliferative effect of D. edulis was associated with reduced tissue (uterine) levels of estradiol (p<0.001). These results suggest that the aqueous extract of D. edulis leaves could be a potential alternative treatment for proliferation-related diseases.